Modeling the Dispersion of Air Pollution Due to Volcanic Eruptions - Sufitri, Yumita; Bachtiar, Vera Surtia; Putra, Alqadri Asri; Nugroho, Sugeng (International Journal of Disaster Management, 2024)
The eruption of Mount Marapi has caused damage to agricultural land and the temporary closure of Minangkabau International Airport. Simulations were conducted using HYSPLIT to detect the initial direction of volcanic ash dispersion. The trajectory analysis from HYSPLIT indicated that the volcanic ash dispersion on December 3, 2023, and January 5, 2024, extended beyond 100 km, while on December 22, 2023, January 19, February 4, and February 23, 2024, the dispersion was less than 100 km. HYSPLIT models indicated that the ash dispersion was directed towards Minangkabau Airport during the closure period. As a result, HYSPLIT can be considered a suitable software for simulating volcanic ash dispersion. Concentration evaluations based on Government Regulation No. 22 of 2022 revealed that several areas exceeded the applicable air quality standards. Validation using data from the HIMAWARI satellite and NASA WorldView indicated similar dispersion direction patterns in the simulation results. However, the Mann-Whitney test revealed significant differences when comparing the concentration outputs from HYSPLIT to PM2.5 levels before and during the eruption, based on PM2.5 monitoring documents from GAW Kototabang. Recommended mitigation measures include prioritizing the volcanic ash hazard zone within a 0-10 km radius from the crater by restricting activities and planning evacuation routes and safe areas away from volcanic ash exposure.